Transcriptome atlases of rat brain regions and their adaptation to diabetes resolution following gastrectomy in the Goto-Kakizaki rat - Brial, François; Le Lay, Aurélie; Rouch, Claude; Henrion, Edouard; Bourgey, Mathieu; Bourque, Guillaume; Lathrop, Mark; Magnan, Christophe; Gauguier, Dominique (Molecular brain, 2025)
Brain regions drive multiple physiological functions through specific gene expression patterns that adapt to environmental influences, drug treatments and disease conditions. To generate a detailed atlas of the brain transcriptome in the context of diabetes, we carried out RNA sequencing in hypothalamus, hippocampus, brainstem and striatum of the Goto-Kakizaki (GK) rat model of spontaneous type 2 diabetes, which was applied to identify gene transcription adaptation to improved glycemic control following vertical sleeve gastrectomy (VSG) in the GK. Over 19,000 distinct transcripts were detected in the rat brain, including 2794 which were consistently expressed in the four brain regions. Region-specific gene expression was identified in hypothalamus (n = 477), hippocampus (n = 468), brainstem (n = 1173) and striatum (n = 791), resulting in differential regulation of biological processes between regions. Differentially expressed genes between VSG and sham operated rats were only found in the hypothalamus and were predominantly involved in the regulation of endothelium and extracellular matrix. These results provide a detailed atlas of regional gene expression in the diabetic rat brain and suggest that the long term effects of gastrectomy-promoted diabetes remission involve functional changes in the hypothalamus endothelium.